Universos: sistema web de auxilio para o ensino superior. - LEOPOLDINO, Guilherme Buzati; BENTO, Jéssica Graciele de Carvalho; ORTEGA, Pedro Igor Ferreira; LIMA, Thais Angélica de Carvalho (138, 2016)
A demanda pela educação superior no Brasil cresceu consideravelmente nos últimos anos, de modo que o ingresso em cursos de graduação é levado atualmente como item obrigatório por estudantes recém-egressos do Ensino Médio, fazendo-os recorrer à internet, onde está disponível uma série de informações relativas ao tema. O problema é que, com a quantidade elevada de dados na rede, raramente um usuário consegue atingir seus objetivos reais de busca sem recorrer a três ou mais fontes, que geralmente focam em questões específicas. Assim, o principal objetivo do presente projeto é auxiliar estudantes e universitários a se integrarem da melhor maneira ao âmbito geral do Ensino Superior, reunindo diversas informações em uma única plataforma. As pesquisas realizadas indicaram grande interesse do público pela proposta do software, o que reforça ainda mais sua relevância social e viabilidade. Os resultados obtidos com o desenvolvimento do projeto atingem os principais objetivos traçados, pois além de facilitarem a busca pelas informações, também proporcionam uma boa experiência aos usuários, suprindo as lacunas localizadas.

The demand for Higher Education in Brazil has grown considerably in the last years, so that entry to graduation courses is took nowadays as acompulsory item for just egressed high school students, doing them to run to internet, where are available a series of information relating to the subject. The problem of the high amount of data on the web is that, rarely an user can achieve its real search objectives without run to three or more sources, that usually focus on specifics issues and disregard the others. Thus, the main objective of this project is to help students (high school and university students) to integrate themselves in the best way to the Higher Education general scope, gathering many information in a single source. The needs pointed out by the analysis of the collected data made possible the definition of the main elements that are part of the system, composed by general information about the institutions, showing their location, available courses and respective periods, counting also with indication of places like bars, clubs, malls, bookstores and gyms, considering the local trends and the diversity characteristic of the public adopted, that shows many divergences as to the main forms of entertainment, besides the recommendation of items related to life quality and well being of users, essential factors to its success and complete development. The results obtained with the development of the project related to the main objectives outlined, besides facilitating the search for information, also provide a good experience to the users, supplying the localized gaps.
Universes: web support system for higher education.
Keywords: Ensino superior; Estudantes; Softwares; Informação e Comunicação